2016
DOI: 10.1007/s10584-016-1623-3
|View full text |Cite
|
Sign up to set email alerts
|

Landslides and synoptic weather trends in the European Alps

Abstract: Landslides present a substantial geomorphological hazard in Alpine regions and there are expectations that climate change will alter their frequency and magnitude in the future. Understanding the spatial distribution and timing of landslides in the context of past change is therefore necessary if we are to assess their future behaviour. Using a regional landslide inventory for the European Alps we analyse the influence of weather types, specifically the COST733 database, on landslides. Monte Carlo permutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…Huggel et al, 2012;Zerathe et al, 2014;Micheletti et al, 2015;Palazón and Navas, 2016;Wood et al, 2016). The premise behind this work is that to explain impacts of changes in climate on Alpine catchment suspended sediment yield, it is necessary to consider both transport capacity and sediment supply.…”
Section: Introductionmentioning
confidence: 99%
“…Huggel et al, 2012;Zerathe et al, 2014;Micheletti et al, 2015;Palazón and Navas, 2016;Wood et al, 2016). The premise behind this work is that to explain impacts of changes in climate on Alpine catchment suspended sediment yield, it is necessary to consider both transport capacity and sediment supply.…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of meteorological synoptic triggering conditions has been addressed through several studies, including those developed in British Columbia (Canada) [16], in Serra do Mar (Brazil) [17], in Italy [18], in the European Alps [19] and in Portugal [20]. Moreover, other authors [21,22] have related the occurrence of landslides with atmospheric patterns at a global scale, such as the North Atlantic Oscillation.…”
Section: Study Areamentioning
confidence: 99%
“…In 2005, Trigo et al (2005) found connections between the NAO index and the occurrence of landslides in Portugal. Wood et al (2016) investigated the synoptic weather trends and landslide in the European Alps. The meteorological control on the distribution of debris flows in Iceland was also investigated by Decaulne and Saemundsson (2007).…”
Section: Introductionmentioning
confidence: 99%